Micro-Ultrasound Imaging for Accuracy of Diagnosis in Clinically Significant Prostate Cancer: A Meta-Analysis - Zhang, Minhao; Wang, Rong; Wu, Yuqing; Jing, Jibo; Chen, Shuqiu; Zhang, Guangyuan; Xu, Bin; Liu, Chunhui; Chen, Ming (Frontiers in Oncology, 2019)
Background: Prostate cancer is a frequently diagnosed malignant solid tumor in men. The accuracy of diagnosis is becoming more and more important in prostate cancer. This meta-analysis evaluated the accuracy of micro-ultrasound in the diagnosis of clinically significant prostate cancer.We searched PubMed, Embase, Web of science and Cochrane Library databases to recruit English studies. The quality assessment of diagnostic accuracy studies-2 protocol was used to evaluate the literature quality. Publication bias was analyzed using Deeks' funnel plot asymmetry test. We calculated the pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and 95% confidence interval (95% CI) in micro-ultrasound imaging for prostate cancer. The results were assessed by summary receiver-operating characteristic curve (SROC). Ultimately, an univariable meta-regression and subgroup analysis, Fagan plot, and the likelihood matrix were conducted.Results: A total of 7 studies containing 769 patients were involved in this meta-analysis. Microultrasound had a pooled sensitivity, specificity, DOR, and an area under the SROC of 0.91, 0.49, 10, and 0.82 respectively. Micro-ultrasound has superior ability to diagnose clinically significant prostate cancer.Micro-ultrasound is a more convenient and cost-effective method in real-time imaging during the biopsy procedure in clinically significant prostate cancer detection. Although microultrasound has promising results, more clinical data and comprehensive analysis are still needed.